PENGARUH STRUKTUR KEPEMILIKAN PERUSAHAAN TERHADAP KUALITAS AUDIT - Bagus Pratama; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2013)
This study aims to examine the effect of ownership structure on audit quality. The research was done by testing the effect of variable ownership concentrations (OwCon), foreign ownership (ForOwn), institutional ownership (InsOwn), and managerial ownership (ManOwn) on audit quality (AuQua). In addition, this study also used two control variables namely firm size (Size) and leverage (Lev). The population used in this study are all companies listed on the Indonesia Stock Exchange (IDX) in the period of 2011. While the sampling method used was purposive sampling method. Overall, the sample used in this study amounted to 166 companies. From the analysis performed in this study, it can be concluded that the all variable OwCon, ForOwn, InsOwn, and ManOwn significantly influence AuQua. So, from four hypotheses that proposed in this study, all of them are accepted.